Phantom-Telles: sistema de medidas ponto a ponto para procedimentos dosimétricos em radioterapia - Oliveira, Leo Sousa Santiago de (2023)
Water phantoms are used to simulate human tissues and to measure various dosimetric parameters in order to ensure the correct radiation exposure of patients. The objective of this work was to develop a point-to-point measurement system to obtain dosimetric parameters of linear accelerator beams used in radiotherapy. For this, a water phantom was built, named phantom-Telles, with an automated system for detector positioning and a calculation model identified as FOCAL. This model uses the transport equation with approximations to interpolate data measured in the phantom-Telles in order to simulate continuous scan measurements made by commercial phantoms. The phantom-Telles was constructed at the Federal University of Rio Grande do Norte, restructured, programmed, and calibrated at the Federal University of Sergipe, and validated at the Real Hospital Português in Recife, through comparisons between dosedepth percentage (PDD) and dose profile curves in radiation fields of 6 MV beams from a Varian-TrueBeam linear accelerator measured with a commercial IBA phantom. The results of the PDD and Profile measurements showed that the data obtained with the phantom-Telles conformed to those obtained with the phantomIBA, with uncertainties of up to 0.005 cm for detector displacements and 0.001 pA for detector measurements. The simulated and measured point-to-point data in the new phantom differed by up to 1% from those obtained by scanning in the phantom IBA. The data set obtained in this work indicates that the phantomTelles has potential for use in quality control and commissioning of linear accelerators.